Critical perspectives on Philip Pullman's His dark materials : essays on the novels, the film and the stage productions - Barfield, Steven; Cox, Katharine, 1976- (Jefferson, N.C. : McFarland, 2011)
"Philip Pullman's epic trilogy remains controversial for its negative depiction of religion. Scholars from various literary, philosophical, and theatrical fields address topics relevant to reading, studying, understanding the work, and its basis in Milton's Paradise Lost; the influence of science fiction on the series; issues of social class, religion, sexuality, and gender; and recent stage productions"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Pullman, Philip, -- 1946-; Young adult fiction, English -- History and criticism; Fantasy fiction, English -- History and criticism; Pullman, Philip, -- 1946- -- Film adaptations; Pullman, Philip, -- 1946- -- Stage history; Allegory; His dark materials; The golden compass; Aufsatzsammlung